Neuroendocrine and Aggressive-Variant Prostate Cancer - Spetsieris, Nicholas (Cancers (Basel), 2020)
SIMPLE SUMMARY: Prostate cancer may in some cases exhibit microscopic and molecular characteristics of a distinct subtype of disease which is referred to as neuroendocrine differentiation. This entity is rarely found in patients initially diagnosed with metastatic disease and most commonly occurs after treatment of prostate cancer in advanced stages with hormonal agents. This specific presentation of the disease is not effectively targeted by the hormonal therapies used in prostate cancer and exhibits an aggressive clinical course. Interestingly, some tumors may have molecular and clinical characteristics of a neuroendocrine tumor subtype, without however exhibiting the respective histomorphologic features. This aggressive-variant prostate cancer (AVPC) subtype is sensitive to platinum-based chemotherapy, without, however, an impressive long-term response. In this review article we provide an overview of neuroendocrine prostate cancer focusing on the AVPC subtype and we approach current treatment options as well as ongoing research efforts. ABSTRACT: In prostate cancer, neuroendocrine (NE) differentiation may rarely present de novo or more frequently arises following hormonal therapy in patients with castration-resistant prostate cancer (CRPC). Its distinct phenotype is characterized by an aggressive clinical course, lack of responsiveness to hormonal therapies and poor prognosis. Importantly, a subset of CRPC patients exhibits an aggressive-variant disease with very similar clinical and molecular characteristics to small-cell prostate cancer (SCPC) even though tumors do not have NE differentiation. This aggressive-variant prostate cancer (AVPC) also shares the sensitivity of SCPC to platinum-based chemotherapy albeit with short-lived clinical benefit. As optimal treatment strategies for AVPC remain elusive, currently ongoing research efforts aim to enhance our understanding of the biology of this disease entity and improve treatment outcomes for our patients. This review is an overview of our current knowledge on prostate cancer with NE differentiation and AVPC, with a focus on their clinical characteristics and management, including available as well as experimental therapeutic strategies.